Design of synchronization control systems for multiple motion axes - Ma, Ye Zhi (2008)
In this report, a Proportional-Integral-Derivative (PID) Control system for synchronization control of multiple motion axes was presented. A DC motor model and the individual closed-loop PID control are firstly presented and investigated. Then, the design of the synchronization control of the two-axis motion system was studied. The performance analyses and simulations by MATLAB to verify its abilities of tracking and synchronization were completed.